2021
DOI: 10.1021/acsenergylett.1c00111
|View full text |Cite
|
Sign up to set email alerts
|

Composition-Dependent Struggle between Iodine and Tin Chemistry at the Surface of Mixed Tin/Lead Perovskites

Abstract: Tin alloying is a promising strategy to reduce lead content in metal halide perovskites solar cells and to modulate the perovskite band gap. Mixed tin−lead perovskites have shown photovoltaic efficiencies approaching those of lead perovskites and improved long-term stability compared to that of pure tin perovskites. We here demonstrate that the recent success of mixed perovskites lies in a composition-dependent struggle between tin and iodine chemistry at the material's surface. Tin oxidation, which plagues ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 79 publications
4
48
0
Order By: Relevance
“…[45] In a recent computational report, surface Sn 4+ defects are also reported to have electron trapping activity in MASnI 3 and are shown to be intimately related to the p-doped bulk and neutral surface Sn vacancies. [36,46] Very recently, it has also been shown that the formation of a 2D layer (consisting of bulky organic cations such as butylammonium, phenethylammonium, etc.) at the interface with 3D Sn perovskites can drastically increase the formation energy of neutral Sn vacancies at the interface, thereby suppressing the formation of Sn 4+ defects.…”
Section: Charge-carrier Recombinationmentioning
confidence: 99%
See 1 more Smart Citation
“…[45] In a recent computational report, surface Sn 4+ defects are also reported to have electron trapping activity in MASnI 3 and are shown to be intimately related to the p-doped bulk and neutral surface Sn vacancies. [36,46] Very recently, it has also been shown that the formation of a 2D layer (consisting of bulky organic cations such as butylammonium, phenethylammonium, etc.) at the interface with 3D Sn perovskites can drastically increase the formation energy of neutral Sn vacancies at the interface, thereby suppressing the formation of Sn 4+ defects.…”
Section: Charge-carrier Recombinationmentioning
confidence: 99%
“…[48][49][50] In case of mixed lead-tin perovskites, Ambrosio et al reported that the formation of Sn 4+ defects is greatly subdued, as the oxidation of triodide is competitively more favored in these materials. [46] This can partly explain the much superior photovoltaic performance of mixed Pb-Sn PSCs (highest efficiency ≈ 21%) as compared to that of pure-Sn PSCs (highest efficiency ≈ 13%). However, the presence of additional extended defects along with such point defects cannot be dismissed, and more complicated effects including defects forming at junctions between impurity phases, as has been observed in pure Pb-based systems, [51] may also be present.…”
Section: Charge-carrier Recombinationmentioning
confidence: 99%
“…One of the critical aspects limiting the performance and the stability of THPs is the facile oxidation of Sn(II) to Sn(IV), 18 , 19 which may induce a large self-p-doping in the perovskite bulk and deep electron trap states at the perovskite surface. 20 22 Experimental reports demonstrate THPs degradation even in well-encapsulated thin films under exposure of light or under elevated temperatures. 23 25 …”
mentioning
confidence: 99%
“…The (001) surface belongs to the most stable perovskite surfaces 47 and has been subject to several studies on the electronic properties of lead- 26 , 28 , 32 and tin-based perovksites. 21 , 22 , 39 , 45 The radial pair distribution function g M–O (r) (M = Sn, Pb), averaged over the AIMD trajectories, indicates a strong interaction of the Sn surface atoms with the water oxygen atoms, as shown by the peak located at 2.43 Å; see Figure 2 a. The g Pb–O (r) of the MAPbI 3 surface comparatively shows a substantially broadened peak centered at around 2.53 Å.…”
mentioning
confidence: 99%
“…In addition, a noticeable shoulder peak appeared at ~631.7 eV in the I 3d 3/2 core level spectra of the Ipristine lm, corresponding to the I 3 − species. These species were assigned to iodide interstitials/V I + iodine Frenkel defects, which form preferentially under V Sn -rich conditions 49 . The almost invisible shoulder peak for the I/Br/Cl perovskite can be attributed to the reduced iodine loss from the perovskite lattice, along with the signi cantly reduced hole concentration (V Sn defects) revealed by the Hall measurements.…”
Section: Resultsmentioning
confidence: 99%